Open Innovation in Developing Regions: An Empirical Analysis across Manufacturing Companies - Lalić, Bojan; Medić, Nenad; Delić, Milan; Tasić, Nemanja; Marjanović, Uglješa (International Journal of Industrial Engineering and Management, 2017)
Even though innovation potential in manufacturing companies from developing countries has been recognized, companies from these countries are more focused on internal than on external sources of innovation. External sources enable open innovation which is a valuable form of innovation that is receiving an increasing attention. Open innovation potential in manufacturing companies from developing countries could be exploited more. The purpose of this paper is to investigate current innovation practice used by manufacturing companies in a specific developing region namely the Autonomous Province of Vojvodina (Serbia). This investigation deepens non-pecuniary inbound form of open innovation. For this purpose, data taken from European Manufacturing Survey are used. The results of the analyses show that manufacturing companies from Vojvodina collaborate with different partners to innovate. Customers represent the most frequent source of innovative ideas even though, overall, the innovation ideas are generated more from internal sources. Article history: Received (23.02.2017); Revised (01.06.2017); Accepted (04.08.2017)